Antitrust in Network industries: The Microsoft case - Liao, Kaishu (Université d'Ottawa | University of Ottawa, 2003)
This paper analyzes the central antitrust and economic issues raised by network industries. Network effects, low marginal costs and other elements constitute special features of network industries to which antitrust enforcement should be adjusted. I discu